Collision Detection Algorithm of Successive Frames for Automated Air Traffic Control - Shaowei Feng; Jing Zhang; Bin Zeng (2010 3rd International Conference on Information Management, Innovation Management and Industrial Engineering, 2010)
The existing collision detection techniques have not addressed the problem of detecting collisions of very fast moving objects involving situations where the instance of collisions may not even be visible to the eyes, occurring between two frames. For this purpose a simple and novel approach have been devised. This is based on the assumption that if two objects pass through the same region in a sufficiently small time window, then we should consider that they have collided. Mathematically this translates into linking the scene geometry of two successive time frames by taking the convex hull of vertex locations of an object at two successive frames. The inter-flame collision detection method in this paper can easily be adapted for determining possible time and/or distance to collision between airplanes.